(untitled) (Global Journal of Human-Social Science, 2013)
For the last few decades, global warming has become a strong threat to human development. The climate change has been affecting on water resources, biodiversity, agriculture, forestry, and public health in specific, and the way of life in general. Nepal is highly vulnerable to the negative impacts of climate change. The crux of the problem for managing climate change adaptation is the rampant poverty. In such context, this study aims to review the key challenges of climate change governance in Nepal and to determine the extent of the Nepal’s climate change governance capacity. The primary data for this study was collected by administering a score-sheet to the extensively experienced persons in the field of environment and/or climate change. This paper concludes that Nepal’s climate change governance capacity is of moderate level and marginally improving since 2010.